Does the L5 spinal nerve move?: anatomical evaluation with implications for postoperative L5 nerve palsy - Ishak, Basem; Kikuta, Shogo; Scullen, Tyler; Iwanaga, Joe; Denis, Daniel J.; Maulucci, Christopher M.; Dumont, Aaron S.; Tubbs, R. Shane (Surgical and radiologic anatomy. [Englische Ausgabe], 2021)
While palsy of the L5 nerve root due to stretch injury is a known complication in complex lumbosacral spine surgery, the underlying pathophysiology remains unclear. The goal of this cadaveric study was to quantify movement of the L5 nerve root during flexion/extension of the hip and lower lumbar spine.
Online publiziert: 24. September 2020
Gesehen am 05.09.2025